An interdisciplinary review of energy storage for communities: challenges and perspectives - Parra, David; Swierczynski, Maciej; Stroe, Daniel I.; Norman, Stuart A.; Abdon, Andreas; Worlitschek, Jörg; O'Doherty, Travis; Rodrigues, Lucélia Taranto; Gillott, Mark C.; Zhang, Xiaojin; Bauer, Christian; Patel, Martin K. (Elsevier, 2017)
Given the increasing penetration of renewable energy technologies as distributed generation embedded in the consumption centres, there is growing interest in energy storage systems located very close to consumers. These systems allow to increase the amount of renewable energy generation consumed locally, they provide opportunities for demand-side management and help to decarbonise the electricity, heating and transport sectors.